Analysis of the Risks arising from Fire Installations in Workplaces using the Ranking Method - Yilmaz, Fatih; Alp, Selcuk; Oz, Beytullah; Alkoc, Ahmetcan (EOS ASSOC, 2020)
The aim of this study is to analyze the risks arising from fire installations in workplaces. It also aims to propose a risk analysis method in the form of a Fire Safety Risk Ranking System for enterprises with a closed work area of more than 1000m(2) in accordance with regulations in Turkey. The relative weights of fire safety factors were determined by Fuzzy AHP. The ranking points of the enterprises were calculated by using the weights obtained with FAHP. From the 45 enterprises where the risk assessment was applied, only 3 enterprises scored 100 full points according to the fire risk ranking method, and 30 enterprises had a score below 80 points. Out of these, 6 scored below 60 points, which is considered a low score. The distribution of enterprises within sectors was not equal. According to the results, only 6.6% of the enterprises are in compliance with legislation and standards, about 67% are inadequate in terms of fire safety and continue to operate under serious fire risks.
Keywords: arising risks; ranking method; fuzzy AHP; fire installatizons; ANALYTIC HIERARCHY PROCESS; SAFETY EVALUATION SYSTEM; PROCESS AHP; MODEL; Engineering